ANALYSIS OF FINANCIAL ASPECT AND NON-FINANCIAL ASPECT FACTORS THAT INFLUENCE THE SHU (SURPLUS) WITH WORKING CAPITAL AS A MODERATING VARIABLE IN KP-RI (EMPLOYEE COOPERATIVE OF THE REPUBLIC INDONESIA) OF SIMALUNGUN REGENCY - Dewi, Christine Nainggolan (International Journal of Public Budgeting, Accounting and Finance, 2018)
The objective of the research was to find out, analyze and empirically prove that Financial Aspects (Independent Capital, Loan Capital, Member Capital, Business Volume and Manager’s Performance) and Non-Financial Aspect (Number of Members) have some influence on SHU (Surplus) and Work Capital as the moderating variable in KP-RI (Employee Cooperative of the Republic of Indonesia) of Simalungun Regency. The population was 39 cooperatives in Simalungun Regency. the data were the financial data from the final statement of RAT (Annual Meeting) of KP-RI of Simalungun Regency from 2012 until 2015. Time series method was used as the research method. The samples were taken by employing census technique with documentation method. The research used multiple linear regression method and Moderated Regression Analysis were applied for the data testing. The results of the research showed that Financial Aspects (Independent Capital, Loan Capital, Member Capital, Business Volume and Manager’s Performance) and Non-Financial Aspect (Number of Members) were proven to partially and simultaneously influenced SHU if KP-RI of Simalungun Regency. Work Capital as the moderating variable was able to strengthen the correlation among financial aspects i.e. Loan Capital, Business Volume and Manager’s Performance with SHU. However, it was not able to strengthen the correlation among financial aspects i.e. Independent Capital and Member’s Loan, and Non-Financial Aspects i.e. number of members with the surplus of KP-RI of Simalungun Regency.